Perbandingan Karkas Dari Beberapa Bangsa Sapi - Cut Aida Fitri (Jurnal Agripet, 2002)
ABSTRACT.The objective of this research was determined how far the comparisons of carcass of those three species. This research were used 57 fattening cow. Which consisting of 19 Aceh (SA) cow. 19 Brahman cross (BX) cow and 19 Friesian Holstein (FH), for 90 days observation time. The attributes that observed include: percentage of carcass weight, percentage of meat weight, percentage of added result, percentage of bone weight, percentage of fat. From each of those multi special of cow, considering each of their weight before cutter. The result of this research are: mean ( SE) of their life weight are: SA 316.00 9.68 kg, BX: 410.16 9.53 kg and FH: 414.37 10.12 kg. Mean ( SE) of carcass percentage are: FH: 53.33 0.83%, SA 55.75 0.67% and BX: 56.28 0.74. Mean ( SE) of meat weight percentage : FH: 69.15 0.74%, BX: 70.91 1.18% and SA: 72.67 1.08%. Mean ( SE) of added result percentage: FH: 25.22 0.57%, BX: 25.33 0.47% and SA: 25.74 0.74%. Mean ( SE) of bone weight percentage: SA: 16.75 00.58%, BX: 19.24 0.72% and FH: 20.91 0.74%. Mean (SE) of fat percentage: SA: 6.94 0.75% , BX: 17.84 0.55%, and FH: 8.21 0.49%. The result of T test of SA carcass, meat and fat weight percentage were not significantly different with BX. SA added result percentage was not significantly different with BX and FH. SA bone weight percentage was signicantly different (P 0.05) with BX. SA carcass, meats and fat weight percentage were significantly different (P 0.05) with FH. SA bone weight percentage was not significantly different with FH. Carcass weight percentage of BX was signicantly different (P 0.05) with FH. Meat, added result meat, bones and fat weight percentage of BX were not sifnificantly different with FH.